Quand l’injonction à la sollicitude appauvrit le travail émotionnel - Bastien Pereira Besteiro (Perspectives Interdisciplinaires sur le Travail et la Santé)
While most academic research on care work shows that it struggles to be socially and economically recognized, home help organizations for the elderly seem, on the contrary, to be appropriating the notion of care in their practice and communications. This is embodied in the benevolent attitude of at-home caregivers, which corresponds to the expectations of the hierarchy and public regarding their occupational know-how. But instead of contributing to the recognition of the richness of the emotional labour of caregivers, the constraint to show exclusively positive emotions impoverishes their work. The requirement to always be happy demands that caregivers hide their emotions and makes it difficult to set boundaries.